A high-efficiency forming method of large- scale aluminum alloy components using fused deposition additive manufacturing based on multi-energy fields. (February 2021) - Wang, Xin; Zhu, Chao; Xie, Haiqiong; Li, Haiqing; Liu, Fei; Ren, Wenju; Tan, Feng
Abstract: In recent years, the metal additive manufacturing technology has become increasingly mature, but there are still some problems in the forming of large-scale aluminum alloy components, like the low efficiency, high cost, and difficulty in controlling stable morphology and quality. This paper, proposed a new method of metal fused-coating additive manufacturing composite variable polarity tungsten inert gas (MFCAM & TIG). The characteristics of this process were introduced in detail, and the synergistic effects of fused-coating with VP-TIG under the combination process were analyzed. By adopting the cathode crushing effect of the VP-TIG arc, the defects including oxide inclusions in the deposition process were effectively avoided; besides, the cathode cleaning effect were realized. Moreover, the forming characteristics of single-layer single-pass sample were studied, and the process range was obtained. Typically, the deposition process was improved to ensure the surface morphological quality of the component in the forming process. On this basis, a typical three-dimensional (3D) sample was made, which further verified the effectiveness of our new combination method of MFCAM & TIG.